Studi Strategik, Kajian Stratejik Ketahanan Nasional Dan Perkembangannya Di Indonesia - Usman, Wan (UI Scholars Hub, 2018)
This paper concern about the meaning of strategic studies, definition of strategy and its developing meaning up to now. The level of strategic studies in the world generally for master degree and doctor degree. Up to now the objective of strategic study are the strategy to solve the problem of solving the threat of peace, and strategy of solving conflict. In Indonesia, strategic studies known as national resilience, which is to solve the threat of national prosperity and security. The method of solving the problem in research are multidiscipline, interdiscipline and transdiscipline. Finally this paper explain about the construction of model to measure the national resilience.